2018
DOI: 10.1002/adom.201701340
|View full text |Cite
|
Sign up to set email alerts
|

Nearly 100% Horizontal Dipole Orientation and Upconversion Efficiency in Blue Thermally Activated Delayed Fluorescent Emitters

Abstract: strong donor. [12][13][14][15] These groups narrow the singlet-triplet energy gap (ΔE ST ) and thus lead to enhanced efficiency in green and blue TADF emitters. The donors have also shown a tendency for their molecular transition dipole moments to preferentially align in the in-plane (horizontal) direction relative to the substrate. [16][17][18] For example, 2,4-bis{3-(9H-carbazol-9-yl)-9H-carbazol-9-yl}-6-phenyl-1,3,5triazine (CC2TA) which features the carbazolylcarbazole donor shows a preferred horizontal di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 90 publications
(50 citation statements)
references
References 34 publications
2
48
0
Order By: Relevance
“…The maximum EQE of the TrzCz1 device was similar to that of BCzTrz with the same donor and acceptor, except for the core structure. [27] Replacement of the phenylc ore with 9-phenylcarbazole maintained the high EQE of the phenylc ore based BCzTrz emitter.T he difference in device performances was observedi nt he electroluminescence (EL) spectra of the TADF devices. The color coordinate of the BCzTrz device was (0.23, 0.42) with am aximum at l = 485 nm at 10 %d oping concentration ( Figure 7).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…The maximum EQE of the TrzCz1 device was similar to that of BCzTrz with the same donor and acceptor, except for the core structure. [27] Replacement of the phenylc ore with 9-phenylcarbazole maintained the high EQE of the phenylc ore based BCzTrz emitter.T he difference in device performances was observedi nt he electroluminescence (EL) spectra of the TADF devices. The color coordinate of the BCzTrz device was (0.23, 0.42) with am aximum at l = 485 nm at 10 %d oping concentration ( Figure 7).…”
Section: Resultsmentioning
confidence: 95%
“…In the conventional TADF emitter with the same diphenyltriazine acceptor and bicarbazole donor,t he diphenyltriazinea cceptorw as in the same plane as the phenylene unit bridging the donor and acceptor. [27] However,t he diphenyltriazine acceptor wasd istortedb ya bout 41-428 in the TrzCz1 and TrzCz2 emitters due to the steric hindrance of the phenylu nit of the 9-phenylcarbazole. Distortion of the diphenyltriazine from the carbazole plane would reduce the degree of conjugation andc ould increase the emission energy of the molecules.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[33] In order to study the effect of donor units on the dipole orientation of the TADF emitters, we developed three D-p-A configured blue emitters of CzTrz, BCzTrz, and TCzTrz by adopting different donors such as carbazole, bicarbazole, and triscarbazole, respectively (Chart 4). [11] The angle dependent PL analysis of the emitters in the DPEPO host at a doping concentration of 10 wt% revealed that TCzTrz and BCzTrz possess a high horizontal emitting dipole ratio of Ca. 95 % and 89 %, respectively, compared to CzTrz (66 %), indicating that the triscarbazole and bicarbazole donors lead to preferential in-plane alignment compared to carbazole due to their rod-like extended linear structure.…”
Section: 35-triazine-based Tadf Emittersmentioning
confidence: 98%
“…These approaches enabled a small DE ST of close to 0 eV and a high PLQY of close to 100 %. [2,[8][9][10][11] In TADF emitters, the emission generally originates from the intramolecular (CT) singlet state (S 1 ) rather than from the local excited state similar to conventional fluorescent emitters. The CT emission commonly shows very broad emission profiles, which is a detrimental factor for the high color purity of the emitters.…”
Section: Design Tactics Of Tadf Emittersmentioning
confidence: 99%